2004
DOI: 10.1159/000078766
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Mast Cells in Benign and Malignant Breast Lesions

Abstract: Background: It has been reported that the number of mast cells was significantly greater in malignant breast carcinomas than in benign breast lesions. This was due to tryptase-containing mast cells while tryptase, chymase-containing mast cells had no effect. However, analysis of mast cells in breast carcinomas and benign breast lesions based on their histological findings remains to be elucidated. Methods: Using immunohistochemical methods morphological examinations of mast cells were undertaken in benign and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Our paired intervention study showed that MDC was significantly higher in patients after neo-adjuvant chemotherapy, this phenomenon could be explained by the inherent role of mast cell in the immune response, that is, chemotherapy may induce tissue damage, and high density of mast cell in tissue after chemotherapy is important for tissue repair. HER-2 is also a key molecule participates in breast cancer and max diameter of cancer and lymph node metastasis were reported to be associated with breast cancer [22, 25]. It is interesting that our data showed that mast cell infiltration is not associated with these factors.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our paired intervention study showed that MDC was significantly higher in patients after neo-adjuvant chemotherapy, this phenomenon could be explained by the inherent role of mast cell in the immune response, that is, chemotherapy may induce tissue damage, and high density of mast cell in tissue after chemotherapy is important for tissue repair. HER-2 is also a key molecule participates in breast cancer and max diameter of cancer and lymph node metastasis were reported to be associated with breast cancer [22, 25]. It is interesting that our data showed that mast cell infiltration is not associated with these factors.…”
Section: Discussionmentioning
confidence: 52%
“…Some scholars believe that the higher the density of mast cells in the breast cancer tissue, the worse the prognosis. Kashiwase et al found that, mast cell density was higher in invasive breast cancer and in breast carcinoma with poor differentiation and poor prognosis than that in fibroadenoma and tubular carcinoma and papillary carcinoma with good prognosis [22]. Some other scholars hold opposing views, they believe that mast cell infiltration suggest the good prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that mast cells (MCs) are involved in the regulation of extracellular matrix degradation, immune response and tumor angiogenesis via releasing numerous bioactive substances such as pro-angiogenic factors, including vascular fibroblast growth factor-2 (FGF-2), platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), interleukin-6 (IL-6) and some non-classical pro-angiogenic factors, for example tryptase [ 7 , 8 ]. Kankkunen et al found that there were significantly more tryptase-containing MCs in malignant breast carcinomas compared to benign lesions, suggesting that MC density is correlated with the extent of tumor growth by promoting angiogenesis [ 9 , 10 ]. Meanwhile, MCs tryptase (MCT) had been found to generate a similar effect as VEGF to stimulate angiogenesis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mast cell infiltration is commonly found in human BrC and their densities have been associated with either the promotion or suppression of tumor growth [ 5 , 17 , 18 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 31 , 41 ]. Among the main documented pro-tumoral mechanisms are the promotion of angiogenesis, invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The MC role in cancer progression is controversial; while some studies associate high tumor MC density with BrC subtypes of good prognosis or with favorable clinical outcomes [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], others find them associated with aggressive features [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. One potential problem of current approaches to elucidate the participation of MCs in BrC progression, is that most studies are observational and correlative, and until now the molecular mechanisms have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%